Theoretical and experimental revision of surface acoustic waves on the (100) plane of silicon - Alexander Tarasenko (Nature Portfolio, 2021)
Abstract The phase velocity dispersion of the surface acoustic waves on a basal plane of Si(100) has been calculated in the whole range of the azimuthal angle of propagation. We present a detailed description of the calculations. These calculations are compared with the experimental data obtained by a laser acoustic method. Our data convincingly demonstrate the existence of a gap in the spectrum of the phase velocities. The gap means that in a definite range of the phase velocities the SAWs are absent in the whole interval of the azimuthal angles. There is an excellent coincidence between the numerical and experimental data.